1982
DOI: 10.1042/cs0620403
|View full text |Cite
|
Sign up to set email alerts
|

Turnover Studies of Human β2-Microglobulin in the Rat: Evidence for a β2-Microglobulin-Binding Plasma Protein

Abstract: 1. 125I-labelled beta 2-microglobulin (beta 2m) was injected into rats and protein or non protein-bound radioactivity was determined in plasma urine and several organs. 2. The observed kinetics differed from those expected according to the bicompartmental model for plasma protein turnover. The difference was attributed to the binding of a part of the tracer to a plasma component. Chromatography of plasma taken after injection of beta 2m showed an additional peak of radioactivity at the 55,000-80,000 daltons po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…However, Nguyen-Simonnet et al [17] obtained results in animal experiments using l25I-P2-m, suggesting that p2-m bound to plasma protein is catabolized in organs other than the kidney (i.e. mainly lung and spleen), whereas free p2-m is eliminated from the kidney.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, Nguyen-Simonnet et al [17] obtained results in animal experiments using l25I-P2-m, suggesting that p2-m bound to plasma protein is catabolized in organs other than the kidney (i.e. mainly lung and spleen), whereas free p2-m is eliminated from the kidney.…”
Section: Discussionmentioning
confidence: 91%
“…Several research findings have demonstrated that plasma contains free p2-m and p2-m bound to a carrier protein [17,18]. If only free p2-m were eliminated from the kidney, whole renal p2-m clearance estimated from renal creatinine clearance, glomerular sieving coefficient for p2-m and plasma total ()2-m concentration would be over estimated, while renal p2-m clearance due to urinary excretion calculated based upon the urinary excreted amount of p2-m and plasma total p2-m concentration would be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…This study, therefore, adds further support to the assumption of a peritubular mode of Prmicroglob ulin removal. Studies on the elimination of human p2-microglobulin in dogs have yielded similar conclusions [19], while in the rat no such mechanism could be demon strated [20] which, however, may be the consequence of the presence of a binding plasma protein for human Prmicroglobulin in rats [21] and, therefore, of an impair ment of the free glomerular filtration of Prmicroglobu lin. For several low-molecular-weight peptide hormones, the existence of a peritubular mode of elimination seems likely [7,22].…”
Section: Discussionmentioning
confidence: 76%
“…As reported elsewhere [7], we found that patients (n = 49) with urinary vol ume <100 ml/day had significantly (p < 0.01) higher plasma p2m concentrations, (40.5 ± 10 mg/1) than patients with daily urinary volume > 100 ml/day (31.1 ± 8.2 mg/1). This is readily explained by the obser vation of Nguyen-Simonet et al [6] that extrarenal catabolism and/or excretion ac counts for only 3% of total metabolic clear ance rate, the rest being eliminated via the kidneys. In view of potential mechanisms of amyloidogenesis it is of interest that extrarenal disposal involves p2m complexes, in which p2m is bound to plasma macromole cules.…”
Section: Are High P2m Levels In Dialysis Patients Merely the Results Omentioning
confidence: 97%
“…In a series of remarkable papers, the Lyon group dem onstrated that in the anephric animal, plasma p2m levels are passively controlled by glomerular filtration rate [6]. This obser vation explains the marked dependence of P2m levels in dialyzed patients on residual urine volume.…”
Section: Are High P2m Levels In Dialysis Patients Merely the Results Omentioning
confidence: 99%